Effect of an Electronic Pill Bottle on Hydroxychloroquine Adherence in Pediatric Lupus: Results of a Novel Direct‐to‐Family Pilot Trial - Rachel L. Randell; Laura E. Schanberg; Claire Beard; Thomas Phillips; Christoph P. Hornik; Michael Cohen‐Wolkowiez; Stephen J. Balevic; with the CARRA Registry investigators (ACR Open Rheumatology)
Objective The objective of this study was to evaluate the preliminary effectiveness of an electronic pill bottle with automated reminders on hydroxychloroquine (HCQ) adherence in children with pediatric systemic lupus erythematosus (pSLE). Methods This was a self‐controlled, open label, direct‐to‐family pilot trial. Children with pSLE treated with HCQ were recruited from the Childhood Arthritis and Rheumatology Research Alliance Registry. All participants received a pill bottle with a sensor in the cap to record openings and provide automated reminders, which were activated after a two‐week run‐in. The primary outcome was a change in adherence measured using the pill bottle over six months. Secondary outcomes included plasma HCQ concentrations and Medication Adherence Self‐Report Inventory (MASRI) scores, collected during four home visits. An exploratory post hoc analysis examined adherence patterns over time. Results Overall adherence was high and did not change over six months (mean ± SD proportion of recorded out of expected pill bottle openings, 0.86 ± 0.20 and 0.89 ± 0.16, P = 0.590). A post hoc analysis grouped participants by adherence pattern. The group with variable adherence, compared with the group with persistent high adherence, had lower dose‐adjusted HCQ concentrations at baseline (0.387 vs 0.627 ng/mL/mg, P = 0.04) and trended toward lower MASRI scores (77.1 vs 93.4, P = 0.09). After six months, there were no differences in HCQ concentrations or MASRI by group. Conclusion Automated reminders did not improve adherence to HCQ for children with pSLE, although the ability to detect effect was limited by a high baseline adherence and small sample size. Post hoc analyses identified different adherence patterns and a subgroup of patients with low HCQ concentrations who could be targeted for future adherence interventions.